THE CONNECTION BETWEEN MASS MEDIA AND NEW CULTURE DURING THE PANDEMIC COVID-19 IN WEST JAKARTA - Mohammad Ismed; Dani Setiadarma; Wahyu Hidayat; Ni Wayan Puja Savitri (Jurnal Ilmiah Publipreneur, 2022)
This article discusses the relationship between mass media coverage and the new culture that emerged as a result of the Covid-19 pandemic. This pandemic has had a tremendous impact, not only from a health perspective, but also from a cultural perspective. Many habits that already exist in society have changed after the consequences of the Covid-19 pandemic. This is certainly something interesting to study, which can provide useful insights for the future. The Covid-19 pandemic gave humans the impetus to adapt to circumstances, one of which was to develop new things. The purpose of this study was to determine the relationship between the mass media and the new culture in order to describe cultural change and how the mass media communicated which had an impact on cultural changeKeyword: Covid, Media Satisfaction, Behavior Change, Culture